Estimating the Trend of Blood Sugar Changes in Diabetic Patients Using the Latent Growth Curve Model a Longitudinal Cohort Study - Yaser Tabarraei; Kamal Azam; Bita Baghbani; Asghar Kazemzadeh; Najme Rahimi; Yousef Dowlatabadi; Houman Kamranian; Afsaneh Vosoghi (Advanced Biomedical Research)
Background: Diabetes, which is characterized by an increase in blood sugar levels, costs a lot of money every year for its treatment and complications due to incorrect treatment and improper control. The purpose of this study was to investigate the trend of blood sugar changes in diabetic patients using the latent growth curve model. Materials and Methods: In this study, data related to diabetic patients participating in Persian cohort study of Sabzevar city were used. To examine intraindividual variation, due to repeated blood glucose measurements for each individual over time, a latent growth curve model was fitted to the data. Analyses were performed with Mplus software version 6.12. Results: Diabetic subjects with an average blood sugar of 168.92 were included in the study. During the study period, their blood sugar increased by an average of 1.74 mg/dL. It was also found that people who had lower blood sugar at the beginning of the study experienced less changes in blood sugar during the study. Conclusion: In this study, the increasing and nonlinear trend of blood sugar in diabetic patients was shown in a longitudinal study with the help of latent growth curve model. Because this model is much easier to interpret the coefficients in it than similar models, it is suggested as a suitable method to find the pattern of variable changes in medical sciences.